Vivências afetivas na formação em psicologia: ser pesquisadora no campo de afecções espinosano - Musha, Elisa Harumi (2023)
This work is the result of a concern that has accompanied me since I joined the teaching profession, regarding the growing precariousness of education. I defend the psychologist's training process as a critical-reflective space in the organization and promotion of human development, beyond a mere sum of theoretical knowledge and access to operational and technical tools. Thus, I sought to address the complexity of training in psychology, from the perspective of the socio-historical psychology that I develop at PUC-SP's Social Exclusion/Inclusion Dialectics Research Center (NEXIN), regarding the understanding of social phenomena in the intertwining of reason and emotion, subjectivity, and objectivity. The research is based on an understanding of psychology training in the context of private universities, analyzing affective experiences mediated by the categories of experience in Lev S. Vigotski and affection proposed by Baruch Espinosa. In addition, I sought to contribute to the methodology of social psychology with the proposal "to be a researcher in the field of Spinoza's affections", with the hope that we can affect each other and be affected throughout our research. Being a researcher in this field means knowing how to deal with the unpredictability of everyday life, having the gumption to dance on the razor's edge when immersed in a mechanized routine that produces sad affections. Thus, supported by Paulo Freire's dialogicity, the research was carried out through interviews and informal conversations with people who make up the body of psychology training (teachers, students, psychology course coordinators and internship supervisors). The analysis showed that these people have the possibility of creating a sensitive body which, by being affected in multiple ways by the paths of training, also becomes capable of affecting, that is, acting and even contributing to the profession. On the other hand, we realize that the great challenge of training in Psychology, posed by 21st century society, is marked by the logic of performance and the extermination of otherness